Antibacterial and Antioxidant Activities of Two Asteracious Species Growing in Pakistan - Shahwar, Durre; Ullah, Saif; Ahmad, Naeem; Ullah, Sami; Akmal Khan, Muhammad (Asian Journal of Chemistry, 2010)
Emergence of drug resistant bacteria and increased oxidative stress are the new havocs for humanity. This study was designed to examine in vitro antibacterial and antioxidant activities of extracts from Xanthium strumarium L. (Asteraceae) and Blumea lacera DC. (Asteraceae). All the plant parts were extracted successively in n-hexane, chloroform and methanol using soxhletapparatus. Antibacterial activity was assessed by agar-well diffusion method. The extracts were also screened for possible antioxidant activity using the 2,2'-diphenyl-1-picrylhydrazyl (DPPH) free radical and total antioxidant activity assay. Methanolextracts were more active than other solvent extracts against test organisms. All the extracts of X. strumarium showed high antibacterial activity. The MICs of all the active extracts were found in the range of 62-500 μg mL-1. In the DPPH assay, the methanol extract of B. lacera was found to be superior to all (IC50 = 0.3 mg mL-1), whereas almost all the extracts particularly the polar ones exhibited antioxidant activity in total antioxidant assay. The correlation studies revealed close relation between antioxidative potential and phenolic content of the extracts. Hence X. strumarium and B. lacera are a potential source for further research activities including isolation of antibacterial and antioxidant components.